2020
DOI: 10.1111/fare.12432
|View full text |Cite
|
Sign up to set email alerts
|

Reorganizing theSingle‐ParentFamily System: Exploring the Process Perspective on Divorce

Abstract: Objective This study investigated how single parents reorganize their family system after divorce. Background Families are dynamic systems that change over time and adapt to crises. Family researchers often approach divorce as a discrete event, however; and little is known about how single parents overcome this crisis and carry on with their lives. Therefore, we investigated the process of how single parents reorganize their households after divorce. Method Qualitative analysis based on grounded theory was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…We found that the possibility of anxiety disorders including SAD, FPM, SP, and GAD was not statistically different for pre-schoolers in single-parent families, pre-schoolers in blended families, and children in stem families compared with those from nuclear families. These results did not support the usual social narratives arguing that children who live in one-parent, blended, and stepfamilies, as well as children who experience parental separation or divorce, carry the highest burden of morbidity (28,29), which was consistent with prior evidence indicating that children in traditional families experience more positive socio-emotional outcomes than children in other family types in Australia (26). The reason for these results may be that even in single-parent families, the care given by their biological parents has not diminished.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found that the possibility of anxiety disorders including SAD, FPM, SP, and GAD was not statistically different for pre-schoolers in single-parent families, pre-schoolers in blended families, and children in stem families compared with those from nuclear families. These results did not support the usual social narratives arguing that children who live in one-parent, blended, and stepfamilies, as well as children who experience parental separation or divorce, carry the highest burden of morbidity (28,29), which was consistent with prior evidence indicating that children in traditional families experience more positive socio-emotional outcomes than children in other family types in Australia (26). The reason for these results may be that even in single-parent families, the care given by their biological parents has not diminished.…”
Section: Discussioncontrasting
confidence: 57%
“…Children who live with both parents in a shared residence arrangement tend to have more optimal mental health outcomes than children who live with only one of their biological parents (27). Additionally, singleparent status is a risk factor for mental disorders in childhood and adolescence (28,29). Compared to children who continuously live with both biological parents, children who live in one-parent, blended, or stepfamilies, as well as children who experience parental separation or divorce are more likely to suffer mental disorders (30).…”
Section: Introductionmentioning
confidence: 99%
“…We do explicitly look into single motherhood after divorce, although other consequences of single parenthood, such as single parenthood by choice or due to bereavement also occur in Belgium (Van Gasse and Mortelmans 2020b;Walsh and McGoldrick 2013). The reasoning behind studying single motherhood after divorce or separation is due to the well-documented increase of stress levels in the period wherein single mothers reorganize their lives to start a single-parent family, illustrating the role and financial strain in this transition process (Booth and Amato 1991;Van Gasse and Mortelmans 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we investigated network support in the process of the reorganization of a single-parent family, as described by Van Gasse and Mortelmans (in press). The process of the reorganization of a single-parent family was described in terms of six phases that people go through in their transition to a single-parent family system.…”
Section: Discussionmentioning
confidence: 99%